Penerapan Konsep Green Economy Terhadap Peningkatan Pendapatan dengan Literasi Digital Sebagai Mediasi pada UMKM di Kota Tebing Tinggi - Harahap, Hastuti Handayani (Economic Development Progress, 2024)
This research is about the Application of the Green Economy Concept to Increasing Income with Digital Literacy as Mediation for MSMEs in Tebing Tinggi City. The research was conducted as field research in MSMEs in Tebing Tinggi City. This research uses a quantitative analytical approach. Data processing in this research uses smartPLS SEM (Partial Least Square - Structural Equation Modeling) software. The results of this research The first hypothesis is accepted that Green Economy (X) has an effect on Digital Literacy (Z). The second hypothesis is accepted that Digital Literacy (Z) influences Increased Income (Y). The third hypothesis is accepted that Green Economy (X) has a significant effect on Increasing Income (Y) through Digital Literacy (Z) as an intervening variable.